Flow-directed loading of block copolymer micelles with hydrophobic probes in a gas-liquid microreactor - Wang, Chih-Wei (Langmuir : the ACS journal of surfaces and colloids, 2013)
We investigate the loading efficiencies of two chemically distinct hydrophobic fluorescent probes, pyrene and naphthalene, for self-assembly and loading of polystyrene-block-poly(acrylic acid) (PS-b-PAA) micelles in gas-liquid segmented microfluidic reactors under different chemical and flow conditions. On-chip loading efficiencies are compared to values obtained via off-chip dropwise water addition to a solution of copolymer and probe. On-chip, probe loading efficiencies depend strongly on the chemical probe, initial solvent, water content, and flow rate. For pyrene and naphthalene probes, maximum on-chip loading efficiencies of 73 ± 6% and 11 ± 3%, respectively, are obtained, in both cases using the more polar solvent (DMF), an intermediate water content (2 wt % above critical), and a low flow rate (∼5 μL/min); these values are compared to 81 ± 6% and 48 ± 2%, respectively, for off-chip loading. On-chip loading shows a significant improvement over the off-chip process where shear-induced formation of smaller micelles enables increased encapsulation of probe. As well, we show that on-chip loading allows off-chip release kinetics to be controlled via flow rate: compared to vehicles produced at ∼5 μL/min, pyrene release kinetics from vehicles produced at ∼50 μL/min showed a longer initial period of burst release, followed by slow release over a longer total period. These results demonstrate the necessity to match probes, solvents, and running conditions to achieve effective loading, which is essential information for further developing these on-chip platforms for manufacturing drug delivery formulations